MOLECULAR GENETIC ASSESSMENT OF BARLEY SELECTION MATERIAL ON ENDURANCE OF COVERED SMUT (USTILAGO HORDEI) - G. V. Vildanova; V. I. Blokhin; I. S. Ganieva; M. M. Lanochkina (Зерновое хозяйство России, 2018)
Lately some innovative selection methods like a marker-assisted selection (MAS) are used together with traditional ones that enable to develop new varieties with qualitative traits faster. MAS include conducting of PCR and analysis of received data to determine the presence of genes alleles with definite traits or DNA-genotyping.  The article gives the results of DNA-genotyping of variety samples of TatRIA selected with four markers of resistance to covered smut (aHor2, UhR450, OPO6780 and OPJ10450). The hybrids F3-F5 were the subjects of study, which were examined by PCR with the use of DNA of selected variety samples. The analysis showed that a genome of one variety sample could possess several gene alleles of resistance to covered smut.  The testing of the sample with PCR-method on locus aHor2 presence showed that less than a half of them turned to be homozygous in susceptibility to covered smut. Thus the analysis helped us to determine economic valuable genotypes for their further use in breeding. Conducted field trials confirmed the received data on genotyping on resistance to covered smut.